Lactation preparation for pregnant women to prevent stunting - Hidayah, Nurul; Fariana, Yuni Riska Nur (Ananda - Health & Education Foundation, 2024)
Background: Stunting, caused by chronic malnutrition during a child's first 1000 days, remains a pressing public health issue in Indonesia. Affecting one in three children under five, stunting hampers physical growth and cognitive development, posing long-term socio-economic risks. The Indonesian government has introduced strategies focusing on maternal and child health, particularly through improving nutrition and healthcare access. However, rural areas face challenges like limited healthcare services and inadequate nutrition education. Case presentation: This program was implemented in Sungai Tabuk, a rural village with high stunting prevalence. The program aimed to educate pregnant women on lactation management and breastfeeding to improve early infant nutrition. Village cadres facilitated pregnancy classes that combined education with hands-on breastfeeding practice. Pre-intervention tests indicated substantial gaps in knowledge, especially about exclusive breastfeeding, while post-intervention assessments showed marked improvements in participants' understanding and skills. Discussion: The involvement of cadres was instrumental in ensuring community participation and sustained educational outcomes. Post-program evaluations revealed that 93% of participants demonstrated improved lactation knowledge and breastfeeding techniques. This highlights the effectiveness of educational interventions in increasing maternal competence, which can lead to better child health outcomes and stunting reduction. However, the program’s short duration and exclusion of other key family members, such as fathers and grandparents, were noted limitations. Conclusion: The program successfully enhanced maternal knowledge and breastfeeding practices as part of stunting prevention efforts. While the results are promising, ongoing support, inclusion of broader family members, and integration with other socioeconomic interventions are necessary for long-term success in reducing stunting in rural communities.